Bleeding Complications after Endovascular Therapy of Cerebral Arteriovenous Malformations - Heidenreich, J.O.; Hartlieb, S.; Stendel, R.; Pietilä, T.A.; Schlattmann, P.; Wolf, K.-J.; Schilling, A.M. (American Journal of Neuroradiology, 2006)
BACKGROUND AND PURPOSE: Intracerebral hemorrhages after embolization of arteriovenous malformations (AVMs) are the most dreaded complications of this well-established therapy. Apart from the known risk factors, our center noticed a high incidence of complications during postinterventional monitoring in medical intensive care units (ICUs) and stroke units.MATERIALS AND METHODS: We report 125 consecutive interventions performed on 66 patients by using flow-dependent microcatheters and n-butyl cyanoacrylate as the embolic agent. Postinterventional intensive care monitoring was performed in an interdisciplinary operative ICU, a stroke unit, or a medical ICU. Patients were compared with regard to bleeding complications, AVM morphology, embolization result, postinterventional monitoring, and demographic factors.RESULTS: Intracerebral hemorrhages occurred in 7 patients. Significant differences in outcome were found between 66 patients monitored in the interdisciplinary operative ICU from medical ICU or stroke unit. This was also true when adjusted for age and extent of AVM reduction by using exact logistic regression. A partial AVM reduction of >60% was a considerable risk factor for hemorrhage (odds ratio [OR] = 18.8; 95% confidence interval [CI] [1.341, not available]. Age was also an essential risk factor. An age difference of 10 years leads to an OR of 2.545 (95% CI [1.56, 7.35]).DISCUSSION:A considerable AVM reduction in one session appears to increase the risk of hemorrhage technically. This suggests a distribution of the interventions in many partial steps.